Speciation in ninespine stickleback: reproductive isolation and phenotypic divergence among cryptic species of Japanese ninespine stickleback. (13th May 2013) - Ishikawa, A.; Takeuchi, N.; Kusakabe, M.; Kume, M.; Mori, S.; Takahashi, H.; Kitano, J.
Abstract: Although similar patterns of phenotypic diversification are often observed in phylogenetically independent lineages, differences in the magnitude and direction of phenotypic divergence have been also observed among independent lineages, even when exposed to the same ecological gradients. The stickleback family is a good model with which to explore the ecological and genetic basis of parallel and nonparallel patterns of phenotypic evolution, because there are a variety of populations and species that are locally adapted to divergent environments. Although the patterns of phenotypic divergence as well as the genetic and ecological mechanisms have been well characterized in threespine sticklebacks, Gasterosteus aculeatus, we know little about the patterns of phenotypic diversification in other stickleback lineages. In eastern Hokkaido, Japan, there are three species of ninespine sticklebacks, Pungitius tymensis and the freshwater type and the brackish‐water type of the P. pungitius – P. sinensis species complex. They utilize divergent habitats along coast–stream gradients of rivers. Here, we investigated genetic, ecological and phenotypic divergence among three species of Japanese ninespine sticklebacks. Divergence in trophic morphology and salinity tolerance occurred in the direction predicted by the patterns observed in threespine sticklebacks. However, the patterns of divergence in armour plate were different from those previously found in threespine sticklebacks. Furthermore, the genetic basis of plate variation may differ from that in threespine sticklebacks. Because threespine sticklebacks are well‐established model for evolutionary research, the sympatric trio of ninespine sticklebacks will be an invaluable resource for ecological and genetic studies on both common and lineage‐specific patterns of phenotypic diversification.